Cognitive Prerequisites for Generative Learning: Why Some Learning Strategies Are More Effective Than Others. Issue 1 (16th July 2020) - Breitwieser, Jasmin; Brod, Garvin
Abstract : This study examined age‐related differences in the effectiveness of two generative learning strategies (GLSs). Twenty‐five children aged 9–11 and 25 university students aged 17–29 performed a facts learning task in which they had to generate either a prediction or an example before seeing the correct result. We found a significant Age × Learning Strategy interaction, with children remembering more facts after generating predictions rather than examples, whereas both strategies were similarly effective in adults. Pupillary data indicated that predictions stimulated surprise, whereas the effectiveness of example‐based learning correlated with children's analogical reasoning abilities. These findings suggest that there are different cognitive prerequisites for different GLSs, which results in varying degrees of strategy effectiveness by age.